Koku Baboni (with Moral lessons) - Onadipe, Kola (African Universities Press, 1965)
Koku ,one of a set of twins is customarily abandoned and left to perish. Is it right to do that? What about our Human Right to Live. Did he survive the ordeal,.....and what was the result of his experience?
Keywords: Juvenile literature-English Language readers-Primary-Fiction-Nigeria (English)